PENERAPAN MODEL PEMBELAJARAN FIRE UP UNTUK MENINGKATKAN HASIL BELAJAR MATEMATIKA SISWA KELAS V UPT SDN 3 TANRUTEDONG KABUPATEN SIDRAP - Huryahtul Jannah; Yonathan S Pasinggi; Kamaruddin (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This Classroom Action Research (CAR) study aimed to determine whether the application of the Fire Up learning model could improve the mathematics learning outcomes of fifth-grade students at UPT SDN 3 Tanrutedong, Sidrap Regency. The subjects were all 36 fifth-grade students and their homeroom teachers. Data collection techniques included observation and tests. Data analysis techniques included data reduction, data description, and conclusion drawing. The results showed that teacher and student activity in Cycle I reached a sufficient (C) category and in Cycle II reached a good (B) category. Students' mathematics learning mastery in Cycle I reached 69.44%, or a sufficient (C) category, and increased to 94.44%, or a good (B) category, in Cycle II. This concludes that the Fire Up learning model can improve the mathematics learning outcomes of fifth-grade students at UPT SDN 3 Tanrutedong, Sidrap Regency.